2021
DOI: 10.1161/strokeaha.120.029593
|View full text |Cite
|
Sign up to set email alerts
|

Early NT-ProBNP (N-Terminal Probrain Natriuretic Peptide) Elevation Predicts Malignant Edema and Death After Reperfusion Therapy in Acute Ischemic Stroke Patients

Abstract: Background and Purpose: We aimed to investigate the relationship between early NT-proBNP (N-terminal probrain natriuretic peptide) and all-cause death in patients receiving reperfusion therapy, including intravenous thrombolysis and endovascular thrombectomy (EVT). Methods: This study included 1039 acute ischemic stroke patients with early NT-proBNP data at 2 hours after the beginning of alteplase infusion for those with intravenous thrombolysis only or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Moreover, blood-based biomarkers are also found to be predictive for unfavorable early (END) and long-term functional outcomes of EVT-treated AIS patients, including interleukin-6, NLR, N-terminal probrain natriuretic peptide, albumin, matrix metalloprotease-9, enascin-c, thioredoxin, ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13, and occludin, etc. ( 2 , 3 , 10 , 31 35 ). We have recently reported that high levels of the pro-resolving protein mediator annexin A1 correlated with 3-month clinical outcomes of AIS patients who underwent successful recanalization by EVT ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, blood-based biomarkers are also found to be predictive for unfavorable early (END) and long-term functional outcomes of EVT-treated AIS patients, including interleukin-6, NLR, N-terminal probrain natriuretic peptide, albumin, matrix metalloprotease-9, enascin-c, thioredoxin, ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13, and occludin, etc. ( 2 , 3 , 10 , 31 35 ). We have recently reported that high levels of the pro-resolving protein mediator annexin A1 correlated with 3-month clinical outcomes of AIS patients who underwent successful recanalization by EVT ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recanalization is often accompanied by cerebral ischemia-reperfusion (I/R) injury, which has been shown as a major cause of early complications, long-term neurological dysfunctions, or even death of AIS patients undergoing EVT ( 2 , 3 ). Innate immunity and acute inflammatory response within the penumbra play important roles in the pathological progression of cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis reported an association between NT-proBNP levels and all-cause mortality (OR 2.43, 95% CI 1.62–3.64) and an association between NT-proBNP levels and cardiovascular mortality (OR 2.01, 95% CI, 1.55–2.61) ( Zhao et al, 2020 ). Considering the NT-proBNP levels in patients who underwent intravenous thrombolysis, one study reported that NT-proBNP levels were associated with 3-month mortality in patients with stroke who underwent intravenous thrombolysis (OR 1.334, 95% CI 1.020–1.745) ( Zhang X. et al, 2021 ). In the present study, NT-proBNP levels were independently associated with 3-month mortality, which is consistent with the findings of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of five studies found that NT-proBNP levels were associated with functional outcomes (OR 1.68, 95% CI 1.13–2.50) ( Otaki et al, 2019 ; Zhao et al, 2020 ). Considering the performance of NT-proBNP in patients who underwent intravenous thrombolysis, a previous study reported a tendency of poor functional outcomes as NT-proBNP levels increased ( Zhang X. et al, 2021 ). In our study, we found an independent association between NT-proBNP levels and poor 3-month functional outcomes in patients who underwent intravenous thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation